Tracking and sorting in the Finnish educational system - Laura Heiskala; Jani Erola (Dynamics of Inequality Across the Life-course (DIAL), 2022)
This report gives a brief overview of educational tracking and sorting in the Finnish educational system. In Finland, students are divided into different tracks relatively late even though between and within-school tracking exists at all educational levels in some forms. In this report, we present descriptive empirical analyses of long-term consequences of educational tracking by social origin using full population Finnish register data. According to our analyses, parental education and parental social class are associated with track choice at upper secondary and tertiary education. Track choice at upper secondary education is also associated with several outcomes at occupational maturity, such as final educational attainment, social class, earnings and unemployment. Track choice at tertiary education partly explains these associations but the coefficients remain statistically significant in most of the cases. Furthermore, our decomposition analyses show a direct effect of social origin on outcomes at occupational maturity which is not explained by track choice at upper secondary and tertiary education.